Collaborative Strategy for the Supply Chain of Rice: A Case Study on Demak and Sukoharjo Regency, Central Java, Indonesia - Adi Djoko Guritno; Novita Erma Kristanti; Megita Ryanjani Tanuputri (agriTECH, 2021)
The problems associated with rice production in Indonesia appear very complicated, due to poor management of the sufficient national rice stock and various unfavorable public policies. Recently, government’s directives on rice importation instigated polemics from several interests, as a result of inappropriate decisions on general rice production, with possible yearly increment. Therefore, there is need to embrace strategy development to balance demand and supply. The purpose of this study was to analyze the rice supply chain in Demak and Sukoharjo, Central Java Province, in an effort to provide effective and collaborative distribution policies at individual levels. In addition, in-depth interviews were conducted for 98 respondents in a bid to acquire relevant and current information for the conceptual framework development. Furthermore, sampling methodologies, termed purposive and snowballing, were applied, followed by the preparation of interview guidelines. The results showed the farmers obtained the lowest revenue margin among other tiers, while several technical challenges were also identified. Consequently, the activities of middlemen with excessive dominant roles in market price determination, were overemphasized, leading to an inefficient supply chain. Meanwhile, government’s position through the Indonesia Logistics Bureau (BULOG) is assumed to be vulnerable in the control of direct supply from farmers or collectors. Based on this study, intense comprehension of rice supply chain was achieved, with further provision of collaborative strategies towards promoting the balance of demand and supply.